Management of digital business transformation - Maksym Babenko; Tetyana Novikova; Olena Khrystoforova; Timur Malafieiev (Фінансово-кредитні системи: перспективи розвитку.)
The article analyzes the importance of digital transformation as an integral part of modern business and the role of effective change management in its implementation. Digital transformation is radically changing traditional business models, creating new opportunities for growth, adapting to rapid technological change, and securing competitive advantages in the digital economy. The success of such transformations largely depends on change management, which helps organizations to smoothly integrate innovations, adapt staff to new approaches, and maintain corporate culture.  The article discusses in detail the main aspects of digital transformation, including the impact of digital technologies on business efficiency, increasing customer focus and process optimization. The article highlights modern approaches to change management, such as creating leadership teams, staff training, developing digital skills, and implementing analytical solutions. Examples of successful cases of digital strategies implementation are provided, which demonstrate the positive impact of transformation initiatives on the market positions of companies.